PHYSICAL DISABILITY AND PHYSICAL ACTIVITY: A REVIEW OF THE LITERATURE ON CORRELATES AND ASSOCIATIONS - Saebu, Martin (European Journal of Adapted Physical Activity, 2010)
The purpose of this article was to examine the literature on correlates and associations of physical activity among adults (age 16-65 years) with physical disabilities. Electronic searches were conducted to identify research articles published from 1980 to 2009. Specific inclusion criteria were identified. The search produced 4,189 articles; however, only 57 met all specified criteria. They represented seven different disability groups, including one cross-over category with two or more disabilities. The International Classification of Functioning, Disability and Health developed by the World Health Organization was used as a structural framework for organising the results. The results revealed a substantial core of research concerning a few disability groups, among them spinal cord injury and multiple sclerosis. Significant correlates were identified in relation to type of disability and functioning, but also among environmental factors (e.g. costs, accessibility, built environment, information and social support) and personal factors (e.g. age, exercise self efficacy, depression, and mental health). Findings are discussed relative to conducting future physical activity research on persons with disabilities.
Keywords: physical activity; exercise; disability; correlates; determinants